Homogenization and miniaturization of habitat structure in temperate marine forests. - Pessarrodona, Albert; Filbee-Dexter, Karen; Alcoverro, Teresa; Boada, Jordi; Feehan, Colette; Fredriksen, Stein; Grace, Sean; Nakamura, Yohei; Narvaez, Carla; Norderhaug, Kjell; Wernberg, Thomas (Global Change Biology, 2021)
Humans are rapidly transforming the structural configuration of the planet's ecosystems, but these changes and their ecological consequences remain poorly quantified in underwater habitats. Here, we show that the loss of forest-forming seaweeds and the rise of ground-covering 'turfs' across four continents consistently resulted in the miniaturization of underwater habitat structure, with seascapes converging towards flattened habitats with smaller habitable spaces. Globally, turf seascapes occupied a smaller architectural trait space and were structurally more similar across regions than marine forests, evidencing habitat homogenization. Surprisingly, such habitat convergence occurred despite turf seascapes consisting of vastly different species richness and with different taxa providing habitat architecture, as well as across disparate drivers of marine forest decline. Turf seascapes contained high sediment loads, with the miniaturization of habitat across 100s of km in mid-Western Australia resulting in reefs retaining an additional ~242 million tons of sediment (four orders of magnitude more than the sediments delivered fluvially annually). Together, this work demonstrates that the replacement of marine forests by turfs is a generalizable phenomenon that has profound consequences for the ecology of temperate reefs., (C) 2021 John Wiley & Sons, Ltd
31 citations (Crossref) [2023-10-31] Place: (C) 2021 John Wiley & Sons, Ltd
Keywords: Australia; Ecosystem; Forests; Humans; Miniaturization; Seaweed; Western Australia; algal turf; climate change; dept.bio; ecological impact; ecosystem; epilithic algal matrix; forest; foundation species; habitat change; habitat structure; human; kelp forest; kelp forests; miniaturization; peer-reviewed; regime shift; seaweed; sediment pollution; species richness; temperate forest